Migração e fecundidade como respostas multifásicas à seca de 2011-2016 no Seridó Potiguar - Isac Alves Correia (2023)
The multiphasic responses are characterized by successive changes of population behavior, including demographics (migration and fertility), as an alternative to deal with social pressures. The 2011-2016’s drought may have stimulated multiphasic responses in Seridó Potiguar, since this region depends on agro pastoral activities, highly influenced by rain, availability of water resources and temperatures. The main objective of this thesis, therefore, will be to identify the demographic responses to droughts based on the combination between migration (migratory flow, average age of migration and types of migration) during the 2011-2016 drought and the change in fertility indicators (Average Age at First Child - AAFC and Interpregnancy Interval - II) in Seridó Potiguar. Therefore, this thesis will use as data sources two household surveys with information on sociodemographic, economic and environmental issues, with sample representation for the urban population of Seridó Potiguar in the years 2017 and 2019, in addition to official statistics such as demographic censuses and data from live births. The methodology consists of Tobit regression models to compare the fertility measures of the treatment groups (women aged 29-49 and 20-34 years in the drought period) with the control groups (women aged 59+ and 20-34 years in the pre-drought period), controlling for socioeconomic, environmental and demographic characteristics, including the condition of migration in the drought period (departure from a semi-arid municipality to the Seridó in the period 2011-2016) to test the hypothesis of multiphasic responses. The results show an increase in flows and the relative share of internal and urban-urban migration in the volume of total migration compared to previous years (2000 to 2010). The analyzes are also consistent with the hypothesis of postponement of fertility in the drought period, where women aged 50+ years in the pre-drought period experienced a younger AAFC (at 24 years old on average) than women aged 29-49 who had the first child during or after the drought (30 years). The results for II also show higher averages of intervals in months for children of women aged 20-24, 25-29 and 30-34 years during the drought (57.9; 82.9 and 104.0 months, respectively), when compared to the births of women's children in the pre period (39.7; 42.5 and 55.6). In addition, the AAFC of women aged 29-49 who had their first child during the drought period has a positive association with perceived temperature increase. In turn, the II for women aged 20-34 years in the drought period is positively associated with the occurrence of a health problem related to the lack of water at home. In regression models for women aged 20-34 years in the 2011-2016 drought period, multiphasic responses were confirmed, with a positive association between migration and postponement. However, for women aged 25-29 years, the association with the emigration of a resident of the household is negative, assuming that the migration of another individual from the household dispenses with the drought response through birth spacing. Another important issue is that even in the pre-drought period, an association was observed between a higher AAFC for women aged 59+ who lived in the urban area of Seridó but who exercised some activity in the rural area, proving the existence of multi-situated households that contemplate strategies of production in both locations (rural and urban) to better take advantage of opportunities. In a scenario of low fertility and of climate change that may increase the severity of periods of drought, the multiphasic responses are increasingly relevant for designing adaptation policies. Furthermore, it is important to consider the possibility of incorporating multiphasic responses to droughts, other types of disasters and other climate shocks in population projections.